The Portrayal of Character Building in American Animation Film Frozen - Rudy Rudy; Sridinda Sarah Swati Hutabarat; Dewi Paskaria Silitonga; Desy Manullang; Yesika Saragih (J-Lalite: Journal of English Studies, 2021)
There is no doubt that having good characters is essential to everyone in society. Character is even a major consideration in the world of education. For this reason, character building is considered important to be explored. By using entertainment media such as movie, this library research concentrates on the character building symbolized through the American animation films Frozen (2013) and Frozen II (2019). Besides the main data from the films, reference sources in the form of books and journals were also used for analysis. Hall’s theory of representation was applied to analyze the data gathered for this study such as dialogs and the description of scenes from the films to identify how the character building is represented through the films as well as to understand the essence of character building. The result showed that the animation films observed in this study can represent good characters through seven values such as bravery, politeness, sacrifice, empathy, curiosity, confidence, and caring. Additionally, this study also reveals that the concept of character is associated with life values, morality and attitude and therefore, character building is significant to shape people with quality in order to create peace and harmony in society. Through this study, it expected that the findings can contribute to the development of the theory in humanities and education and it can provide better understanding to people about character building through American animated films.